Operon structure and cotranslational subunit association direct protein assembly in bacteria - Shieh, Yu-wei; Minguez, Pablo; Bork, Peer; Auburger, Josef Johannes; Guilbride, D. Lys; Kramer, Günter; Bukau, Bernd (Science, 2015)
Proximity best for building protein complexes - The synthesis of protein subunits and their assembly into a fully functional complex are generally thought to be two distinct processes. Shieh et al. studied the synthesis and assembly of the luciferase complex in Escherichia coli. Organization of the luciferase subunits LuxA and LuxB side by side into an operon promotes their colocalized synthesis and assembly into an active enzyme complex. Indeed, the association between the subunits occurs as they are being synthesized on ribosomes, which helps order the sequence of subunit interactions. - Science, this issue p. 678 - Assembly of protein complexes is considered a posttranslational process involving random collision of subunits. We show that within the Escherichia coli cytosol, bacterial luciferase subunits LuxA and LuxB assemble into complexes close to the site of subunit synthesis. Assembly efficiency decreases markedly if subunits are synthesized on separate messenger RNAs from genes integrated at distant chromosomal sites. Subunit assembly initiates cotranslationally on nascent LuxB in vivo. The ribosome-associated chaperone trigger factor delays the onset of cotranslational interactions until the LuxB dimer interface is fully exposed. Protein assembly is thus directly coupled to the translation process and involves spatially confined, actively chaperoned cotranslational subunit interactions. Bacterial gene organization into operons therefore reflects a fundamental cotranslational mechanism for spatial and temporal regulation that is vital to effective assembly of protein complexes. - Protein subunit interaction and assembly in bacteria occur as the subunits are being synthesized on the ribosome. - Protein subunit interaction and assembly in bacteria occur as the subunits are being synthesized on the ribosome.
Gesehen am 17.06.2020